Five-Year Follow-Up of Clinical Outcomes with an Anatomic Dual-Mobility Acetabular System: A Multicenter Study - Dubin, Jeremy (Arthroplast Today, 2020)
BACKGROUND: The dual-mobility implant system has been shown to increase impingement-free range of motion and decrease dislocation risk by increasing the effective head size. In addition, the anatomic dual-mobility (ADM) cup offers relief between the acetabular shell rim and the iliopsoas tendon. This study was designed to review a series of hips implanted with the ADM acetabular cup to examine clinical outcomes after 5 years of implantation at multiple orthopaedic centers. METHODS: We retrospectively queried our prospectively collected total joint arthroplasty registry for patients who underwent total hip arthroplasty with an ADM cup from January 2008 to December 2012 at 4 different orthopaedic institutions and who had minimum 5-year follow-up. Harris Hip Scores and visual analog scale scores were evaluated. Postoperative complications, dislocations, and revisions for any reason were recorded. RESULTS: A total of 142 patients had a mean follow-up of 5.7 years (range: 5.0 to 8.0 years). Radiographic analysis showed no radiolucent lines, osteolysis, or acetabular loosening. There were no dislocations in this patient series. Two (1.2%) hips required a revision because of adverse local tissue reactions related to corrosion from a recalled modular neck stem, but this was unrelated to the ADM cup. The mean Harris Hip pain scores increased from 17 points preoperatively to 39 points at the most recent follow-up (P < .001). The mean Harris Hip function score increased from an average of 29 points preoperatively to 38 points at the most recent follow-up (P < .001). The mean visual analog scale score showed patient improvement from 6.5 preoperatively to 1.2 postoperatively (P < .001). CONCLUSIONS: ADM prostheses were designed to reduce the risk of dislocation by increasing the size of the effective femoral head. In this multicenter study of ADM cups used in primary total hip arthroplasty, we demonstrated good clinical and radiographic outcomes, no dislocations, and no revisions at midterm 5-year minimum follow-up. Patient-reported outcome measures were also improved, supporting the use of this implant.